The cruise of the Canoe Club - Alden, W. L. (William Livingston), 1837-1908; Rogers, W. A. (William Allen), 1854-1931 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Cruise of the Canoe Club" by W. L. Alden is a novel written in the late 19th century. This adventurous tale follows four boys$1 (BCharley Smith, Tom Schuyler, Harry Wilson, and Joe Sharpe$1 (Bwho embark on a canoeing journey filled with excitement, challenges, and camaraderie. The narrative captures their preparations, the trials they face in acquiring canoes, and their thrilling experiences as they navigate various waterways. The opening of this novel introduces us to the boys' ambitious plan for a canoe cruise, revealing their initial challenges with finances and canoe selection. They meet the Commodore of a canoe club for advice and receive conflicting recommendations from several canoeists regarding the best type of canoes. As the young adventurers come together to discuss their findings and make decisions, the foundation for their friendship is set against a backdrop of the great outdoors. Ultimately, they begin to navigate their newly acquired canoes, leading to both entertaining mishaps and thrilling escapades on the water, hinting at the many adventures that lie ahead. (This is an automatically generated summary.)s
Release date is 2022-06-16
Richard Hulse, hekula03 and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Canoes and canoeing -- Juvenile fiction